Art 21 [videorecording (DVD)] : art in the twenty-first century. Season five - Atlas, Charles; Tatge, Catherine; Sollins, Susan; Dowling, Susan; Kentridge, William, 1955-; Weems, Carrie Mae, 1953-; Salcedo, Doris, 1958-; Koons, Jeff, 1955-; Heilmann, Mary, 1940-; Maier-Aichen, Florian, 1973-; Cao, Fei, 1978-; Shonibare, Yinka, 1962-; et al. (Art21 Inc. : Distributed by PBS Distribution, 2009)
Through in-depth profiles and dynamic behind-the-scenes footage featuring artists speaking directly about their inspirations and ideas, Season Five shows a broad range of artistic practice, technical innovation, and experimentation, from artists tackling large-scale collaborative projects in hangar-like studios to those working in the quiet of more intimate studio settings.